Study on the Composite EM Scattering from Sea Surface with Ship Based on Kd-Tree Accelerated Hybrid Model - Ye Zhao; Xin-Cheng Ren; Peng-Ju Yang (International Journal of Antennas and Propagation)
A hybrid model based on the geometrical optics and physical optics (GO-PO) method and facet-based asymptotical model (FBAM) for the composite EM scattering from sea surface with ship has been previously developed. But, the GO-PO method faces a difficult problem that the lower efficiency in testing the visibility of patches to the incident and reflected waves. Hence, to improve the computation efficiency of the GO-PO method, a kd-tree accelerated hybrid model is presented in this paper. The kd-tree method firstly carries out the intersection test between the ray and the bounding box where the patch is located before the operation between the ray and the patch. If the distance parameters of the bounding box do not meet the requirement, the ray is not necessary to enter the bounding box, which can reduce the needless intersection tests. Numerical results show that the proposed kd-tree accelerated hybrid model could improve the efficiency about three times and could be applied to the study of composite EM scattering characteristics of electrically large sea surface with a ship target.